Tourism potentials of selected medieval fortresses in Bosnia and Herzegovina - Mirić, Ranko; Drešković, Nusret; Avdić, Boris; Nezirović, Senada (Journal for Geography, 2017)
The medieval heritage in the context of cultural and historical tourism in Bosnia and Herzegovina is often neglected, but the practice of other European countries shows that this segment of history can be exploited on a very high level. This is primarily related to large objects in the form of fortresses, which generally have a dominant position over the surrounding area. In Bosnia and Herzegovina there are a large number of such forts (over a hundred), which testify to the turbulent medieval past. The fact is also that a large number of such facilities are in an inadequate state, but there are also those who may or already have their tourist function. Within this paper, four examples of medieval forts in Bosnia and Herzegovina - two in the Bosna River valley and two in Northeast Bosnia, from the aspect of their tourism attractiveness and degree of valorization have been analyzed. The methodology in this paper is based on detailed empirical research conducted through very extensive field observation, with the application of combined qualitative and quantitative comparative method of tourism valorization. The particular method used in the paper was based on the application of GIS cartographic models for adequate spatial representation of the study objects.
Keywords: medieval fortresse; Vranduk; Doboj; Zvornik; tourism valorization